Integrated Transcriptomic and Machine Learning Analysis Identifies EAF2 as a Diagnostic Biomarker and Key Pathogenic Factor in Parkinson’s Disease - Peng H; Cheng Y; Chen Q; Qin L (International Journal of General Medicine)
Haoran Peng,1,* Yanwei Cheng,2,* Qiao Chen,3 Lijie Qin2 1Department of Neurology, People’s Hospital of Henan University, Henan Provincial People’s Hospital, Zhengzhou, Henan, 450003, People’s Republic of China; 2Department of Emergency, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, People’s Hospital of Henan University, Zhengzhou, People’s Republic of China; 3Nursing Department, Air Force Medical Center, PLA, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lijie Qin, Department of Emergency, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, People’s Hospital of Henan University, No. 7 Weiwu Road, Jinshui District, Zhengzhou, Henan, 450003, People’s Republic of China, Email qinlijie1819@163.comBackground: Parkinson’s disease (PD) is a prevalent neurodegenerative disorder characterized by the progressive loss of dopaminergic neurons. This study aims to discover potential new genetic biomarkers for PD.Methods: Transcriptome data from a total of 56 patients with PD and 61 healthy controls were downloaded from the Gene Expression Omnibus (GEO) database. Differential gene expression (DEG) analysis, weighted gene co-expression network analysis (WGCNA), and three machine learning algorithms (LASSO, Random Forest, SVM-RFE) were employed to identify pivotal PD-associated genes. Additionally, RT-qPCR experiments were conducted to validate our findings in clinical specimens. Functional enrichment analysis and Gene Set Enrichment Analysis (GSEA) were performed to explore the functional and pathway mechanisms of the identified genes in PD. Molecular docking studies revealed potential small-molecule drug targets for the key genes.Results: The results from the three machine learning algorithms identified ELL-Associated Factor 2 (EAF2) as a key gene in PD. Gene expression analysis indicated that EAF2 is significantly downregulated in PD patients, and the receiver operating characteristic (ROC) analysis validated the diagnostic potential of EAF2. The results from RT-qPCR on clinical specimens confirmed the findings from public database analyses. Functional enrichment analysis suggested that EAF2 is involved in dopamine biosynthesis and synaptic transmission for PD pathology. Additionally, EAF2 expression correlated significantly with immune cell infiltration. Furthermore, molecular docking results indicated that Acalabrutinib, Tirabrutinib Hydrochloride, and Ibrutinib are potential targeted therapeutic agents for EAF2.Conclusion: These findings underscore EAF2 as a novel diagnostic biomarker and potential therapeutic target for PD, warranting further mechanistic studies and clinical validation.Keywords: Parkinson’s disease, EAF2, transcriptomics, machine learning, immune modulation